ESG Investing: Evaluating the Financial Performance of Sustainable Portfolios - Pramitasari, Dini Ayu (Universitas Tanjungpura, 2024)
This research examines the financial performance of ESG (Environmental, Social, Governance) portfolios compared to traditional non-ESG portfolios, focusing on their returns, volatility, and risk management. A qualitative approach was employed, utilizing a literature review and analysis of historical data from ESG reports and financial databases, particularly the FTSE4Good Index. The findings indicate that ESG portfolios significantly outperform traditional investments, with an average annual return exceeding conventional portfolios by approximately 4.3%. Additionally, ESG portfolios exhibit lower volatility and reduced drawdowns during market downturns, demonstrating their resilience and risk mitigation capabilities. The research concludes that investing in companies with high ESG ratings not only aligns with ethical standards but also enhances long-term financial performance. These insights underscore the growing relevance of sustainable investing in contemporary financial markets. Investors are encouraged to integrate ESG criteria into their strategies while remaining vigilant about potential challenges, such as greenwashing and variability in ESG ratings. Future research should address existing gaps in understanding the long-term impacts of ESG investing across different sectors and regions to further validate these findings.